2002
DOI: 10.1590/s0100-736x2002000400005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and antigenic analysis of Babesia bigemina isolates from five geographical regions of Brazil

Abstract: A molecular epidemiological study was performed with Babesia bigemina isolates from five geographical regions of Brazil. The genetic analysis was done with random amplification of polymorphic DNA (RAPD), repetitive extragenic palindromic elements-polymerase chain reaction (REP-PCR) and enterobacterial repetitive intergenic consensus sequences-polymerase chain reaction (ERIC-PCR) that showed genetic polymorphism between these isolates and generated fingerprinting. In RAPD, ILO872 and ILO876 primers were able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Given the specificity of such techniques, the detection and genetic characterization of this disease can be achieved simultaneously (Hulton et al, 1991;Harris et al, 1996;da Silva et al, 2004). Madruga et al (2002) demonstrated the use of ERIC-PCR in the characterization of a protozoan parasite. The authors conducted a molecular epidemiological study to identify the genetic diversity present among Babesia bigemina protozoa isolated from five states in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Given the specificity of such techniques, the detection and genetic characterization of this disease can be achieved simultaneously (Hulton et al, 1991;Harris et al, 1996;da Silva et al, 2004). Madruga et al (2002) demonstrated the use of ERIC-PCR in the characterization of a protozoan parasite. The authors conducted a molecular epidemiological study to identify the genetic diversity present among Babesia bigemina protozoa isolated from five states in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…A diversidade genética tem sido demonstrada para espécies do gênero Babesia entre isolados de diferentes regiões geográficas, sendo esta responsável pelo polimorfismo antigênico que determina heterogeneidade intra-específica (Allred 2001). Considerando-se a extensão territorial do Brasil e o número expressivo de bovinos, pode-se inferir a existência de acentuadas variações no perfil molecular entre diferentes isolados ou cepas regionais (Madruga et al 2002), o que justifica a necessidade de que sejam obtidos microrganismos de referência e colocados à disposição para estudos de epidemiologia molecular das populações autóctones.…”
Section: Introductionunclassified
“…Pseudomonas (LOWS et al, 1994), Shigella (LIU et al, 1995), Listeria (JERSEK et al, 1996), Brucella (TCHERNEVA 1996), Babesia bigemina (MADRUGA et al, 2002), Bartonella (RODRIGUEZ-BARRADAS et al, 1995), S.aureus (MATTOS, 2005) e Leishmania (LEAL, 2010).…”
Section: Pesquisadores Utilizaram Eric-pcr Como Ferramenta De Diferenmentioning
confidence: 99%